Single-Molecule Analysis of the Recognition Forces Underlying Nucleo-Cytoplasmic Transport - Rangl, Martina (2013)
To move molecules across the nuclear envelope they have to overcome the selective barrier of the nuclear pore which is formed by nucleoporins with FG repeats. For this, they are chaperoned by shuttling receptors that interact with FG nups thereby passing the barrier with an unresolved mechanism. We explored the molecular binding and dissociation of this process using single molecule force spectroscopy showing that no energetic cost is required for translocation.